2020
DOI: 10.3390/membranes10120416
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Incorporated Polysulfone Substrate for Flat Sheet Thin Film Nanocomposite Pressure Retarded Osmosis Membrane

Abstract: This study focuses on the development of flat sheet thin film nanocomposite (TFN) pressure retarded osmosis (PRO) membranes for the enhancement of osmotic power generation by the incorporation of laboratory-synthesised graphene oxide (GO) into the polysulfone (PSf) polymer matrix. A series of membranes containing different weight percent of GO (0, 0.1, 0.25, 0.5 and 1.0 wt%) were fabricated via a phase inversion method with polyethylene glycol (PEG) as the pore forming agent. The results show that the TFN-0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Moreover, A strong peak was observed around 3000 cm −1 for CH 3 stretching. These functional groups have confirmed the presence of polysulfone 47 . FTIR spectra for PSf/ZnO showed low‐intensity absorption peaks of ZnO nanoparticles at around 3500 and 1595 cm −1 .…”
Section: Resultsmentioning
confidence: 66%
“…Moreover, A strong peak was observed around 3000 cm −1 for CH 3 stretching. These functional groups have confirmed the presence of polysulfone 47 . FTIR spectra for PSf/ZnO showed low‐intensity absorption peaks of ZnO nanoparticles at around 3500 and 1595 cm −1 .…”
Section: Resultsmentioning
confidence: 66%
“…To achieve a low value of the structural parameter corresponding to a lower ICP, a highly porous, thin, and less tortuous structure is needed. In previous studies on minimizing the ICP, structural parameter was reduced by optimizing the material composition [6,7] and incorporating nanoparticles [8][9][10][11] by the phase inversion method, and by employing a novel fabrication strategy using electrospinning [12][13][14]. The most effective results were Membranes 2022, 12, 166 2 of 12 achieved with a polymeric fibrous support fabricated by electrospinning that decreased the value of the structural parameter and the tortuosity to 66 µm and 1.2, respectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…Basically, polysulfone (PSf) is the most commonly used polymer in PRO membranes. It possesses good mechanical, thermal and chemical stabilities [ 12 ]. In addition, the high solubility of PSf makes it an ideal selection for polymer-blend membranes since other polymers or additives can be co-dissolved with it, thus enhancing the membrane’s performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the incorporation of the highest dosage, i.e., PEG 1500, tended to negatively affect the membrane’s mechanical properties. Zhou et al [ 12 ] modified a PSf-FO substrate by blending it with methoxypolyethylene glycol, together with different M W of PEG (200, 500, 1000 and 1900 gmol −1 ). Their work demonstrated that the water fluxes of the modified membranes increased dramatically when a PEG with a M W of 500 gmol −1 was used to modify the PSf substrate.…”
Section: Introductionmentioning
confidence: 99%